Moving forward in carcinogenicity assessment: Report of an EURL ECVAM/ESTIV workshop. (December 2017) - Corvi, Raffaella; Madia, Federica; Guyton, Kathryn Z.; Kasper, Peter; Rudel, Ruthann; Colacci, Annamaria; Kleinjans, Jos; Jennings, Paul
Abstract: There is an increased need to develop novel alternative approaches to the two-year rodent bioassay for the carcinogenicity assessment of substances where the rodent bioassay is still a basic requirement, as well as for those substances where animal use is banned or limited or where information gaps are identified within legislation. The current progress in this area was addressed in a EURL ECVAM- ESTIV workshop held in October 2016, in Juan les Pins. A number of initiatives were presented and discussed, including data-driven, technology-driven and pathway-driven approaches. Despite a seemingly diverse range of strategic developments, commonalities are emerging. For example, providing insight into carcinogenicity mechanisms is becoming an increasingly appreciated aspect of hazard assessment and is suggested to be the best strategy to drive new developments. Thus, now more than ever, there is a need to combine and focus efforts towards the integration of available information between sectors. Such cross-sectorial harmonisation will aid in building confidence in new approach methods leading to increased implementation and thus a decreased necessity for the two-year rodent bioassay. Highlights: Need to develop novel alternative approaches to the two-year rodent cancer bioassay Insight into carcinogenicity mechanisms is essential to drive new developments. Direct efforts towards the integration of all available information, also across endpoints. Cross-sector harmonisation to build confidence in new approach methods